2010
DOI: 10.1016/j.biomaterials.2010.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of adhesive complex coacervates modeled after the sandcastle glue of Phragmatopoma californica for craniofacial reconstruction

Abstract: Craniofacial reconstruction would benefit from a degradable adhesive capable of holding bone fragments in three-dimensional alignment and gradually being replaced by new bone without loss of alignment or volume changes. Modeled after a natural adhesive secreted by the sandcastle worm, we studied the biocompatibility of adhesive complex coacervates in vitro and in vivo with two different rat calvarial models. We found that the adhesive was non-cytotoxic and supported the attachment, spreading, and migration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 27 publications
0
99
0
1
Order By: Relevance
“…Moreover, it was found that the highly condensed complex coacervates significantly increased Figure 12.5 Potential medical applications of adhesive materials inspired by mussels (blue), tube worms (red), and brown algae (green). (A) Bone adhesive for the reconstruction of craniofacial features [67], (B) adhesive-coated vascular scaffold promoting endothelial cell proliferation [68], (C) vascular sealant for surgical adjunctive leakage control [69], (D) adhesive for immobilization of pancreatic transplants on liver surface [70], (E) adhesive-coated biologic meshes for hernia repair [71], (F) sealant for fetal membrane repair [72], (G) adhesive-coated titanium bone implant promoting osteoblast proliferation [66], (H) adhesive for skin incision closure [73], and (I) adhesive-coated biologic scaffold for Achilles tendon repair [74]. All these biomimetic adhesives have been successfully tested in vitro with cultured cells or in vivo in animal models.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was found that the highly condensed complex coacervates significantly increased Figure 12.5 Potential medical applications of adhesive materials inspired by mussels (blue), tube worms (red), and brown algae (green). (A) Bone adhesive for the reconstruction of craniofacial features [67], (B) adhesive-coated vascular scaffold promoting endothelial cell proliferation [68], (C) vascular sealant for surgical adjunctive leakage control [69], (D) adhesive for immobilization of pancreatic transplants on liver surface [70], (E) adhesive-coated biologic meshes for hernia repair [71], (F) sealant for fetal membrane repair [72], (G) adhesive-coated titanium bone implant promoting osteoblast proliferation [66], (H) adhesive for skin incision closure [73], and (I) adhesive-coated biologic scaffold for Achilles tendon repair [74]. All these biomimetic adhesives have been successfully tested in vitro with cultured cells or in vivo in animal models.…”
Section: Applicationsmentioning
confidence: 99%
“…Moreover, a biodegradable version of the adhesive coacervate was designed by replacing the APMA/acrylamide copolymer by an amine-modified collagen hydrolysate [86]. This adhesive coacervate was used to repair rat calvarial bone defect and was capable of maintaining three-dimensional bone alignment in freely moving rats over a 12 week indwelling period [67]. Histological evaluation demonstrated that the adhesive was gradually resorbed and replaced by new bone with an inflammatory response commensurate with normal wound healing.…”
Section: Adhesives Based On Other Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, the synthetic adhesive was shown to be non-cytotoxic using live ex vivo human amniotic membranes. A similar condensed polyelectrolyte adhesive formulation was biocompatible and effectively secured and maintained alignment of rat skull fragments during healing 20 .…”
Section: Introductionmentioning
confidence: 99%
“…These qualities have sparked interest in the sandcastle worm glue (Shao et al, 2009), as well as in other marine bioadhesives, notably the byssal adhesive plaques of mytilid mussels , as sources of natural materials and design principles for underwater adhesives. The potential applications of these bioinspired synthetic adhesives include the repair of wet living tissues (Winslow et al, 2010;Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%